Q-learning based fault estimation and fault tolerant iterative learning control for MIMO systems - Wang, Rui; Zhuang, Zhihe; Tao, Hongfeng; Paszke, Wojciech (1975- ); Stojanovic, Vladimir
This paper proposes a Q-learning based fault estimation (FE) and fault tolerant control (FTC) scheme under iterative learning control (ILC) framework. Due to its repetitive property of the demand on the control actuator, ILC is sensitive to actuator faults. Moreover, unknown faults could bring uncertainties to the system dynamics, which is a challenge to the control performance.
Keywords: iterative learning control; fault estimation; fault tolerant control; Q-learning; MIMO systems